CAN-catalyzed microwave promoted reaction of indole with Betti bases under solvent-free condition and evaluation of antibacterial activity of the products. Issue 21 (2nd November 2017) - Pegu, Choitanya Dev; Nasrin, Sheikh Benazir; Deb, Mohit L.; Das, Deep Jyoti; Saikia, Kandarpa K.; Baruah, Pranjal K.
ABSTRACT: CAN-catalyzed reaction of Betti bases with indoles under microwave irradiation gives 3-( α, α -diarylmethyl)indoles. Better yield of the products, especially when one of the aryl ring is phenol were achieved. The reaction is performed in solvent-free condition. The antibacterial studies of the synthesized compounds were performed and some of the compounds showed good activity against Methicillin-resistant Staphylococcus aureus bacteria. GRAPHICAL ABSTRACT: